(untitled) (Research, Society and Development, 2021)
The study analyzed the physical-chemical and microbiological parameters carried out by the Autonomous Water and Sewage Service (AWSS) of the Municipality of Alvorada D’Oeste, Rondônia, Brazil. The parameters analyzed were: pH, turbidity, free residual chlorine, total coliforms (TC), thermotolerant coliforms (TTC) and heterotrophic bacteria. The values of hydrogen potential (pH) were obtained with a digital pH meter. The analyzes were carried out the 2013 to 2019. The turbidity and free residual chlorine values were obtained according to the method of the Practical Manual of Water Analysis of the National Health Foundation (FUNASA). To determine the microbiological parameters, PetrifilmTM plates (3MTM do Brasil Ltda) were used, following the manufacturer’s guidelines. The analyzed values were compared with reference values described in Consolidation Ordinance nº. 5, of September 28, 2017, of the Ministry of Health (MS) which sets the standards for potability of water intended for human consumption. The results varied for all parameters evaluated: pH (3.11 to 8.24), turbidez (0.02 to 3,01), TC (0 to 100%), TTC (0 to 100%) and heterotrophic bacteria (85 to 100%). The values obtained for free residual chlorine were the only parameter to follow the reference values. The highest contamination for TC and heterotrophic bacteria were reported in 2019, higher the limits established in Brazilian legislation. Thus, the water was characterized as unfit for consumption and requires severe control for TC and heterotrophic bacteria.